2013
DOI: 10.1038/mi.2012.128
|View full text |Cite
|
Sign up to set email alerts
|

Th17 cells confer long-term adaptive immunity to oral mucosal Candida albicans infections

Abstract: Oropharyngeal candidiasis (OPC) is an opportunistic infection caused by Candida albicans. Despite its prevalence, little is known about C. albicans-specific immunity in the oral mucosa. Vaccines against Candida generate both Th1 and Th17 responses, and considerable evidence implicates IL-17 in immunity to OPC. However, IL-17 is also produced by innate immune cells that are remarkably similar to Th17 cells, expressing the same markers and localizing to similar mucosal sites. To date, the relative contribution(s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
209
0
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(223 citation statements)
references
References 59 publications
6
209
0
8
Order By: Relevance
“…Consistent to this data, it has been also previously shown that Rag -/-mice clear the primary OPC infection without much immunopathology 27 . Under these conditions, compensatory mechanisms dependent on IL-17A producing innate immune cells have been shown to clear the infection in Rag-/-mice 17,29,30 . Taken together, although IL-17A produced by Th17 cells and neutrophil recruitment are playing a protective role at initial phases of infection, excessive production of TNF-α and other cytokines by Th17 cells, and the continued presence of neutrophils causes exacerbated immunopathology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent to this data, it has been also previously shown that Rag -/-mice clear the primary OPC infection without much immunopathology 27 . Under these conditions, compensatory mechanisms dependent on IL-17A producing innate immune cells have been shown to clear the infection in Rag-/-mice 17,29,30 . Taken together, although IL-17A produced by Th17 cells and neutrophil recruitment are playing a protective role at initial phases of infection, excessive production of TNF-α and other cytokines by Th17 cells, and the continued presence of neutrophils causes exacerbated immunopathology.…”
Section: Discussionmentioning
confidence: 99%
“…Although commensals such as C. albicans contribute to modulation and exacerbation of other oral inflammatory conditions, the mechanisms by which dysbiosis occur during opportunistic infections are unclear. Besides the known role of adaptive Th17 cells in memory response to C. albicans 17 , their role in initiation and perpetuation of inflammation pathology during chronic infections remain unclear. Furthermore, oral inflammatory diseases such as Sjogren's syndrome and periodontitis are associated with Th17 mediated pathology.…”
Section: Introductionmentioning
confidence: 99%
“…45,163,164 Th17 cells secrete numerous cytokines including IL-17A, IL-17F and IL-22, and play vital roles for immune protection against C. albicans at the majority of mucosal sites in the body. 165,166 The importance of Th17 cells in anti-Candida responses is not only portrayed by data from mice models, but also from human patients. Patients with deficiency in Th17-mediated adaptive immunity frequently suffer from chronic mucocutaneous candidiasis.…”
Section: Prrs Of Neutrophils and Monocytes/macrophagesmentioning
confidence: 99%
“…This observation suggests that the most important impact of IL-17A occurs early, whereas at later stages other factors may come into play. It should be noted, however, that IL-17RA Ϫ/Ϫ mice do not recover from candidiasis even after long-term infections (7,38), though to our knowledge, IL-17A Ϫ/Ϫ mice have not been tested in this regard. It is also possible that DAY286-IL-17A-infected mice fail to reach a threshold level of IL-17A because they are cleared rapidly during the first 4 days.…”
Section: Discussionmentioning
confidence: 98%